Lanthanum Gadolinium Oxide: A New Electronic Device Material for CMOS Logic and Memory Devices - Pavunny, Shojan P. (Materials (Basel), 2014)
A comprehensive study on the ternary dielectric, LaGdO(3), synthesized and qualified in our laboratory as a novel high-k dielectric material for logic and memory device applications in terms of its excellent features that include a high linear dielectric constant (k) of ~22 and a large energy bandgap of ~5.6 eV, resulting in sufficient electron and hole band offsets of ~2.57 eV and ~1.91 eV, respectively, on silicon, good thermal stability with Si and lower gate leakage current densities within the International Technology Roadmap for Semiconductors (ITRS) specified limits at the sub-nanometer electrical functional thickness level, which are desirable for advanced complementary metal-oxide-semiconductor (CMOS), bipolar (Bi) and BiCMOS chips applications, is presented in this review article.